Measurement of body fluid proteins by polyacrylamide gel electrophoresis. Issue 12 (December 1982) - Johnson, MH; Thompson, EJ
Abstract : A development of the disc polyacrylamide gel electrophoretic system of Ornstein and Davis, which has been applied to the analysis of unconcentrated cerebrospinal fluid, is described. Modifications to the scanning densitometer have improved the signal:noise ratio of the gel scanning system. Using this technique, we have studied the dye-binding properties of albumin, and of beta- and gamma-globulins, and have shown that reproducible quantification of proteins can be achieved. The advantages of electrophoretic methods over immunochemical methods of quantification are discussed.